ENABLING CHILDREN WITH VULNERABILITIES TO PURSUE THEIR EDUCATIONAL ASPIRATIONS: PROSPECTS AND CHALLENGES - Kaur Kalra, Gurneet; Modi, Kiran (International Journal of Child, Youth and Family Studies, 2025)
In India, millions of vulnerable children, particularly those without parental care and living in alternative care settings, and girls from vulnerable sections of society, face significant barriers to accessing quality education. This compromises their fundamental right to education and often leaves their potential unfulfilled. There are also many cross-sectional barriers, such as poverty, gender, caste, and social norms, that reduce opportunities for education. Despite strong legislative and policy mandates in India that emphasise the government’s obligation to protect children’s rights and ensure access to education, gaps persist. Inadequate education hampers children’s overall well-being and development, leaving them unprepared for independent living. This paper highlights the efforts of Udayan Care, a practitioner organization, in regard to improving educational access and outcomes for vulnerable young people. It highlights the role of practitioners in two key programs run by Udayan Care when it comes to supporting academic pursuits and their effects on life outcomes for the recipients of its two programs: Udayan Ghars (Sunshine Homes), a residential program for children without parental care; and Udayan Shalini Fellowship, a program to support girls from underserved families through higher education and leadership. This paper explores the systematic and sociocultural barriers to education for children in care and for young adolescent girls in the communities, and demonstrates how individualised support, mentoring, and a trauma-informed approach can transform their lives. Findings are based on internal program evaluations and practitioner insights and experiences. This paper also offers recommendations to empower vulnerable children through comprehensive education and skill-building initiatives. These best practices demonstrate the transformative power of tailored interventions in shaping the lives of marginalised children and creating a foundation for their independent and successful futures.